Analytical and experimental characterization of sub-half micron MOS devices - Chew, Johnny Kok Wai. (2008)
We present in this thesis the characterization of deep submicrometer (the device channel length ranges from 0.25um to l.Oum) lightly-doped drain (LDD) pMOSFETs operating in a Bi-MOS structure. The Bi-MOS structure is essentially a device operating with its source-body junction forward biased. Consequently, there is an additional current component, the lateral bipolar current, flowing beneath the principal MOS current.